The Effectiveness of Solution-Focused Brief Counseling Group with Miracle Question Technique to Enhance Students' Self-Disclosure - Agungbudiprabowo; Tsabitah Rizqi Atikasari; Caraka Putra Bhakti (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Self-disclosure plays an important role in adolescents' social life, helping them strengthen social relationships, increase social support, and improve their quality of life; however, many students still keep the bad experiences they have experienced to themselves. Students feel uncomfortable if others know their problems, and students are closed about their personal problems. This study aims to determine the effectiveness of solution-focused brief counseling group counseling with the miracle questions technique to improve student self-disclosure at State Junior High School 1 Sleman. The type of research used in this study is an experiment with a pre-experimental research design, using the one-group pretest-posttest design model. The subjects of the study were 6 eighth-grade students at State Junior High School 1 Sleman, selected using purposive sampling. Self-disclosure was measured using a self-disclosure scale that has been validated for its reliability. The data analysis technique used was a t-test. The results of the study showed that the average score increased from 70.3 (low category) to 89.6 (medium category), with a difference of 19.3 points. The hypothesis test results showed a Sig. value. (2-tailed) = 0.001 < 0.05, which can be interpreted as the group counseling solution-focused brief counseling miracle questions technique is effective in increasing student self-disclosure at State Junior High School 1 Sleman. The results of the study can be used as an alternative for guidance and counseling teachers in increasing student self-disclosure through group counseling services with a solution-focused brief counseling approach miracle questions technique. This approach can be integrated into school counseling programs to foster students' social-emotional development. Keywords: self-disclosure, group counseling, solution-focused brief counseling, student